THE POTENTIAL OF LACTIC ACID BACTERIA ISOLATES FROM MERAWANG CHICKEN INTESTINE TYPICAL OF BANGKA BELITUNG AS PROBIOTIC CANDIDATES - Shinta Ahsaniyah; Henny Helmi; Rahmad Lingga (Universitas Medan Area, 2023)
The improvement of egg production efficiency and health remains a challenge in the cultivation of native chickens. The production of feed on farms requires significant costs, which can account for 60-70% of the total production expenses, making it essential to optimize feed efficiency in the chicken's digestive system. Furthermore, the traditional free-range farming of native chickens Merawang in Bangka Belitung, where they are allowed to roam freely in the backyard or garden, makes it difficult to control their development and health. To address these issues, efforts can be made by harnessing the potential of Lactic Acid Bacteria (LAB) present in the digestive system of native chickens to be used as probiotics. The objective of this research was to obtain potential isolates of lactic acid bacteria from native chickens Merawang as probiotic candidates. The study was carried out experimentally in four stages, namely isolation, characterization, confirmation test, and probiotic potential test. The research results indicate that there were 6 isolates with potential as probiotics, namely AM3, AM7, AM12, AM14, AM20, and AM25. These six isolates showed potential as probiotic bacteria because their lactic acid content in a medium meets the applicable standards, ranging from 0.79% to 1.84%. The isolates that performed the best as candidate probiotic bacteria were AM14, AM20, and AM25. The identified bacteria in the digestive system of native chickens belong to the Genus Lactobacillus.